TRENDS IN THE DEVELOPMENT OF FOREIGN ECONOMIC ACTIVITY IN UKRAINE AT THE PRESENT STAGE - Iziumtseva, Natalia; Korobka , Vladislava (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2021)
The article considers the issue of foreign economic activity (FEA) of Ukraine. Today, the Ukrainian economy is deeply integrated into the global system of international division of labor both as a seller and as a buyer of goods and services. In such circumstances, the issue of foreign trade is extremely important for economic development and that is why the development of such an area as foreign economic activity is one of the main tasks assigned to the state bodies of our state.In this work, in order to reveal the main trends in foreign economic activity at the present stage, the dynamics of exports and imports of goods and services for the period 2016-2020 was analyzed, the commodity structure of exports and imports of goods and services and the most influential partner countries. Foreign trade significantly affects the growth of the country's GDP as the main source of income for financial entities. Scholars and practitioners have proven that the export-import activity of the state has a positive impact on the country's GDP growth, especially in conditions of high productivity and competitiveness of domestic products.The results of this study were obtained through the collection and analysis of analytical information posted on the official website of the State Statistics Service of Ukraine (Gosstat) and the Ministry of Economy, Trade and Agriculture of Ukraine (Ministry of Economy), and other scientific publications.The research allowed to identify the main problems that have a negative impact on the development of export-import operations and, as a result, the economy as a whole and offer some recommendations for further development and improvement of the current state of foreign economic activity of domestic enterprises and, in general, states.